Effectiveness of education interventions designed to improve nutrition knowledge in athletes: A systematic review - Tam, R.; Beck, K. L.; Manore, M. M.; Gifford, J.; Flood, V. M.; O`Connor, H. (Sports Medicine, 2019)
Background: A range of nutrition education strategies are used to assist athletes to improve nutrition knowledge. Evaluation of nutrition education interventions guides the delivery of efficacious nutrition education for athletes. Aim: Our aim was to systematically review sport/general nutrition education interventions delivered to athletes, and to evaluate their effectiveness. Methods: A search was conducted using terms related to nutrition knowledge, athletes, education, and intervention. Included studies had to be conducted in athletes (all calibres), use a scored nutrition knowledge assessment tool, and measure knowledge before and after a nutrition education intervention. Peer-reviewed and unpublished theses were included. Results: Thirty-two manuscripts (randomised controlled trial, n = 13; single-arm pre/post design, n = 19) met the inclusion criteria. Participants (n = 2180; mean age 17.4 ± 1.7 years) were mostly female (66.1%), university-level (56.3%) athletes based in the US (75%). Comparison of different education methods was limited since the majority of interventions (n = 28/36, 77.8%) used face-to-face education. Most intervention conditions (n = 19) had a total contact time of < 300 min (5 h). The majority of interventions (n = 30, 85.7%) reported significant knowledge improvement, with a mean increase of 16.1 ± 0.7% (mean effect size 1.72; range 0.4-17.1). Only 15.6% of studies used well-validated knowledge assessment tools (more than three types of validity or reliability testing). Conclusions: Most interventions reported a significant improvement in nutrition knowledge. Unfortunately, the wide range of knowledge assessment tools with limited validation, and the predominant use of face-to-face interventions, prohibits identification of the most effective modality and dose for nutrition education in athletes.